Efektivitas Metode Pembelajaran Bermain Peran Terhadap Hasil Belajar IPS di SDN Karanganyar 2 - Aldiyansah, Ryan; Nur'afifah, Uci Ulfa; Dimas, Arifian (Global Education Journal, 2023)
Education is the key for a country to excel in global competition. Education is considered the most strategic field in realizing social welfare. Therefore, education is an important thing for a country to progress and needs to be prioritized, especially elementary school education because it is a foundation for children, both science and character education because in elementary school character education is very important to form a child's character that is good, responsible, honest, and disciplined. The role-playing method is learning through the development of students' imagination and appreciation by students playing a character, both living and dead. This method develops appreciation, responsibility, and skills in using the material being studied. This research was conducted at SDN Karanganyar 2. This study uses a quantitative approach, pre-experiment design, one group pretest-posttest. The sample of this study was a saturated sample of 30 respondents. The prerequisite test used a normality test with the Kolmogorov-Smirnov formula and a homogeneity test was carried out to determine whether the data was homogeneous or not. Hypothesis testing used a paired one sample t-test. The results of this study indicate that there is an influence on the results of social studies learning at SDN Karanganyar 2. This is proven by the results of the paired sample t-test obtained a sig. (2-tailed) value of 0.000 which is smaller than 0.05. So, there is an influence of the use of role-playing methods on social studies learning outcomes at SDN Karanganyar 2